Caste Transformation, Intracultural Communication, and Social Structure Dynamics in Kei Society, Southeast Maluku-Indonesia - Rumra, Mohammad Yamin (Journal of Ecohumanism, 2024)
This study investigates the system of social stratification and intracultural communication in the Kei people of Southeast Maluku, Indonesia, which is based on centuries-old caste traditions. Kei society is divided into three main classes: mel-mel (nobles), ren-ren (middle class), and iri-ri (lower class), each of which has roles and rights governed by local customary law, Larwul Ngabal. This caste system has created a recognized social balance despite certain dominance and hegemony. This research uses an ethnographic approach with a focus on direct observation, in-depth interviews, and document analysis to explore how stereotypes and social stratification are maintained through intracultural communication. The findings show that Kei people use language and cultural symbols to reinforce their caste position, while modernization and electoral politics open space for changes in social dynamics. The results of this study provide insights into how local communities adapt to modernization and democratization while maintaining traditional cultural structures. The implications of this study underscore the importance of understanding the dynamics of intracultural communication in the context of social stratification to maintain social order and promote inclusiveness in the social development of Kei society.